Exploring and Enhancing the User Experience when Living with Incontinence - Granström, Anna; Rempling, Johanna (My University, 2020)
Many people have, or will, experience involuntary urine leakage at some point in their lives. Despite this fact, living with incontinence and using absorbing incontinence pads, has not been studied from a user-experience (UX) point of view, especially not beyond functionality. This study aimed to explore the user experience when living with incontinence today - important aspects for the desired experience and translating user needs and desires into a product concept. The study consisted of two phases, the first aimed to explore and understand the experience by involving women using incontinence products. Interviews and a creative workshop were the main activities in this phase. The collected data was analysed and resulted in formulating a UX goal: Enhancing the experience of control in the situation. This goal was based on an analysis of emotions connected to the experience and problems identified and presented in the user journey, all with a connection to the desire to be in higher control. Personas were formulated to communicate the main aspects the users value; safety, integrity, support, accessibility and practicality. Phase two aimed to develop concepts and evaluate these concepts with users. Several different ideation and rapid prototyping methods were performed. This was followed by a formative evaluation session to understand which parts of the concepts could give the biggest impact on meeting the UX goal. Phase two resulted in the final concept consisting of user experience guidelines and a product concept. The guidelines explain what contribute to enhance the desired experience, connected to three important areas; gaining awareness, managing everyday life and using protection. A product concept was created to communicate how to interpret the guidelines, including a digital guide and design proposals of assortment, wrap, packaging and pad. The final concept is the result of research performed from a user experience perspective. It includes aspects ranging from functionality to users’ values and dreams of how they want their life with incontinence to be. The material is supposed to inspire future work towards an enhanced user experience when living with incontinence which could improve many people’s quality of life.